Crushing It!: How Great Entrepreneurs Build Business and Influence--And How You Can, Too - Vaynerchuk, Gary (HarperBusiness, an imprint of HarperCollins Publishers, 2018)
In his 2009 book Crush It, Gary Vaynerchuk insisted that a vibrant personal brand was crucial to entrepreneurial success. Now Gary explains why that's even more true today, offering his perspective on what has changed in the last nine years and what principles remain timeless. He also shares stories from other entrepreneurs who have grown wealthier -- and not just financially -- than they ever imagined possible by following Crush It principles. The secret to their success (and Gary's) has everything to do with their understanding of the social media platforms and their willingness to do whatever it took to make these tools work to their utmost potential. Gary dissects every current major social media platform so that anyone, from a plumber to a professional ice skater, will know exactly how to amplify his or her personal brand on each. He offers both theoretical and tactical advice on how to become the biggest thing on old standbys like Twitter, Facebook, YouTube, Instagram, Pinterest, and Snapchat; podcast platforms like Spotify, Soundcloud, iHeartRadio, and iTunes; and other emerging platforms such as Musical.ly. For those with more experience, Crushing It! illuminates some little-known nuances and provides innovative tips and clever tweaks proven to enhance more common tried-and-true strategies. Crushing It! is a guide to building your own path to professional and financial success and a blueprint to living life on your own terms.